Investigating the effect of morphology on the terrestrial gaits of amphibious fish using a reconfigurable robot - Gevers, Louis; Gupta, Astha; Paez, Laura; Fu, Qiyuan; Standen, Emily; Ijspeert, Auke (Bioinspiration & biomimetics, 2025)
The relationship between morphology and locomotion performance in amphibious fish remains poorly understood, particularly in axial-appendage-based and appendage-based movements. To address this, we introduce Polymander, a reconfigurable robot capable of mimicking Polypterus -like walking and mudskipper-like crutching, enabling systematic investigation of body length and limb movement. Using a CPG-driven controller, we optimize locomotion patterns via multi-objective optimization in simulation, comparing resulting Pareto fronts across different morphological configurations. Our results reveal that (1) mudskipper-like crutching is better suited for short bodies, while Polypterus -like walking is better suited for longer bodies; (2) symmetric anterior-to-posterior motion of the limbs is optimal for crutching, while increased anterior limb movement benefits Polypterus -like walking; and (3) sufficient limb strength is necessary for crutching but less so for walking, where axial bending mitigate its effects. Overall, our findings provide a potential explanation of why Polypterus and mudskippers adopt their distinct gaits, emerging as optimal solutions for their morphology within the broader space of all possible gaits.